Double play [compact disc, unabridged] - Parker, Robert B., 1932-2010 (New Millennium Audio, 2004)
Joseph Burke is hired as bodyguard to a spoiled twenty-five year-old woman. This story intertwines with the story of baseball player, Jackie Robinson.